2017
DOI: 10.1161/circresaha.117.311441
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Regulatory Mechanism of Smooth Muscle α-Actin Expression by NRG-1/circACTA2/miR-548f-5p Axis

Abstract: These results suggest that circACTA2 mediates NRG-1-ICD regulation of α-SMA expression in HASMCs via the NRG-1-ICD/circACTA2/miR-548f-5p axis. Our data provide a molecular basis for fine-tuning α-SMA expression and VSMC contraction by transcription factor, circular RNA, and microRNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(94 citation statements)
references
References 22 publications
1
93
0
Order By: Relevance
“…As a representative circRNA, cerebellar degeneration‐related protein 1 antisense ( CDR1as ) is the sponge of miR‐7 in the embryonic zebrafish and has been reported to be related to brain dysfunction and many cancers, such as HCC and gastric cancer . Accordingly, an increasing number of studies has revealed that the circRNA‐miRNA‐target gene regulatory network might have profound implications for understanding diseases, especially cancers . For example, a recent study shows that circ‐ZNF609 acts as an endogenous miR‐615‐5p sponge to inhibit miR‐615‐5p activity, increasing myocyte‐specific enhancer factor 2A (MEF2A) expression and ameliorating vascular endothelial dysfunction .…”
Section: Functions Of Circrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…As a representative circRNA, cerebellar degeneration‐related protein 1 antisense ( CDR1as ) is the sponge of miR‐7 in the embryonic zebrafish and has been reported to be related to brain dysfunction and many cancers, such as HCC and gastric cancer . Accordingly, an increasing number of studies has revealed that the circRNA‐miRNA‐target gene regulatory network might have profound implications for understanding diseases, especially cancers . For example, a recent study shows that circ‐ZNF609 acts as an endogenous miR‐615‐5p sponge to inhibit miR‐615‐5p activity, increasing myocyte‐specific enhancer factor 2A (MEF2A) expression and ameliorating vascular endothelial dysfunction .…”
Section: Functions Of Circrnasmentioning
confidence: 99%
“…[21][22][23][24] Accordingly, an increasing number of studies has revealed that the circRNA-miRNA-target gene regulatory network might have profound implications for understanding diseases, especially cancers. 25,26 For example, a recent study shows that circ-ZNF609 acts as an endogenous miR-615-5p sponge to inhibit miR-615-5p activity, increasing myocyte-specific enhancer factor 2A (MEF2A) expression and ameliorating vascular endothelial dysfunction. 27 Zhong et al 28 found that circ-MYLK is not only related to the stage and grade of the cancer but can also work with miR-29a and relieve the suppression of target vascular endothelial growth factor A (VEGFA), a key member of the VEGFA/VEGFR2/ Ras/ERK signaling pathway.…”
Section: Mirna Sequestrationmentioning
confidence: 99%
“…RNA was synthesized by in vitro transcription as previously described by Sun et al (30). PCR primers including T7 promoter sequences of RBM5 39 UTR were designed and amplified from T24 cell line genomic DNA.…”
Section: Rna Synthesis and Biotin Pull-downmentioning
confidence: 99%
“…Less is known regarding NRG-1-ICD, with the majority of information derived from studies in neurons. Here the authors demonstrate that NRG-1-ICD functions as a transcriptional activator in SMCs through a stable complex with Ikzf1 to induce expression of a non-coding circRNA that functions to suppress miRNA-mediated repression of αSMA 9 . Collectively, NRG-1 modulates SMC phenotype via release of both its intracellular domain and extracellular EGF-like domain.…”
mentioning
confidence: 93%
“…al 9 . assessed the role of the intracellular domain of the epidermal growth factor family member, neuregulin-1 (NRG-1-ICD) on SMC αSMA expression.…”
mentioning
confidence: 98%